2002
DOI: 10.1007/s00264-002-0372-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the surgical results of expansive laminoplasty for cervical spondylotic myelopathy

Abstract: We studied the outcome of expansive laminoplasty in 37 patients with cervical spondylotic myelopathy. Patients were divided into two groups according to the recovery rate (RR) -a 'good' group (n=19), and a 'fair' group (n=18). Patients in the good group showed a greater pre-operative Japanese Orthopaedic Association (JOA) score, a greater compression ratio, and a larger Pavlov ratio (P<0.05). The presence of high signal intensity on MRI proved to be of no prognostic importance.Résumé Nous avons étudié le résul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 23 publications
0
19
2
Order By: Relevance
“…Tomosato [21] demonstrated patients with a longer duration of symptoms had inferior neurological recovery. However, Fessler and Chung reported the duration of symptoms did not affect surgical outcomes [4,9]. In our study, there was no significant difference in neurological recovery in patients with different pre-operative durations of symptoms.…”
Section: Change Of Lower Limb Function Score With Timecontrasting
confidence: 39%
See 1 more Smart Citation
“…Tomosato [21] demonstrated patients with a longer duration of symptoms had inferior neurological recovery. However, Fessler and Chung reported the duration of symptoms did not affect surgical outcomes [4,9]. In our study, there was no significant difference in neurological recovery in patients with different pre-operative durations of symptoms.…”
Section: Change Of Lower Limb Function Score With Timecontrasting
confidence: 39%
“…Surgical decompression is recommended for patients with moderate to severe disease [1]. Studies have been done to evaluate the results of different treatment methods, namely sub-total corpectomy, laminectomy and laminoplasty [6,13,15,20], and factors affecting the surgical outcomes [3,4,11,18,21]. However, these assessments tend to be of a more global perspective, looking at a composite score for upper limb, lower limb and bladder and bowel function.…”
Section: Introductionmentioning
confidence: 99%
“…Fifthly, the average RR obtained from this study was lower than that reported previously. According to previous reports [3,16,[22][23][24][25], the average RR ranged from 47.1 to 67.6%. Factors affecting neurological recovery have also been reported to include age, signal change of the spinal cord on MRI and segments of spinal compression [4-11, 22, 25, 26].…”
Section: Discussionmentioning
confidence: 91%
“…However, Chung et al reported that the presence of high signal intensity on MRI proved to be of no prognostic importance [14], while Morishita et al reported that evaluation of the median nerve SSEP was useful for prediction of the prognosis in the surgically treated patients [15].…”
Section: Discussionmentioning
confidence: 99%